Job-to-Job Flows in the Great Recession - Hyatt, Henry; McEntarfer, Erika (American Economic Review, 2012)
We develop prototype job-to-job flow measures to provide new evidence on labor turnover and earnings dynamics in the Great Recession. We find a sharp drop in job mobility in the Great Recession, much sharper than the previous recession, and higher earnings penalties for job transitions with an intervening nonemployment spell. Focusing on residential construction separators in particular, we find increasing rates of industry change and higher earnings penalties from job change in the Great Recession.